Evaluation of adjuvant carboplatin chemotherapy in the management of surgically excised anal sac apocrine gland adenocarcinoma in dogs. (24th October 2013) - Wouda, R. M.; Borrego, J.; Keuler, N. S.; Stein, T.
Abstract: There is no widely accepted standard of care for canine anal sac apocrine gland adenocarcinoma (ASAGAC). Surgery alone is inadequate in many cases, but the benefit of adjuvant chemotherapy is not well established. The primary objective of this retrospective study was to evaluate the role of carboplatin chemotherapy in the post‐operative management of ASAGAC. Seventy‐four dogs with naturally occurring ASAGAC underwent surgery. Forty‐four dogs received adjuvant carboplatin and 30 did not. Median overall survival (OS) was 703 days. Median time to progression (TTP) was 384 days. Only primary tumour size and lymph node metastasis at diagnosis significantly impacted the outcome. Differences in OS and TTP, between the dogs that received adjuvant carboplatin and those that did not, failed to reach statistical significance. Treatment of progressive disease, whilst not limited to chemotherapy, significantly prolonged the survival. This study shows that adjuvant carboplatin chemotherapy is well tolerated and may have a role in the management of dogs with ASAGAC.